Insertion sequences and sequence types profile of clinical isolates of carbapenem-resistant A. baumannii collected across India over four year period. Issue 7 (July 2020) - Vijayakumar, Saranya; Anandan, Shalini; MS, Dhiviya Prabaa; Kanthan, Kalaiyasi; Vijayabaskar, Sumitha; Kapil, Arti; Ray, Pallab; Sistla, Sujatha; Bhattacharya, Sanjay; Wattal, Chand; Thirunarayan,; Deotale, Vijayshri; et al.
Abstract: Objectives: Acinetobacter baumannii emerged as a major nosocomial pathogen responsible for infections. In this study, we report the molecular characterization, association of insertion sequences and sequence types of clinical isolates of carbapenem resistant A. baumannii . Materials and Methods: A total of 763 non-duplicate isolates of A. baumannii received from 8 centres across India during January 2014 to December 2017 were studied. Susceptibility testing was done by Kirby-Bauer method. PCR was performed for detection of extended spectrum β-lactamases, metallo β-lactamases, oxacillinases and IS Aba1 . Mapping PCR was performed to identify the position of IS Aba1 with respect to bla OXA-23 like and bla OXA-51 like gene. MLST was performed to identify the sequence type. Whole genome sequencing was done to decipher the genetic arrangement of IS Aba1 with bla OXA-23 like and with bla OXA-51 like. Results: All the isolates were resistant to imipenem and meropenem. bla OXA-23 like was the predominant carbapenemase. All isolates were positive for IS Aba1 . The common sequence types were ST848, ST451 and ST1305 which belongs to International clone II. Whole genome sequencing showed considerable variation in the insertion site location. Conclusions: In conclusion, high prevalence of bla OXA-23 like in A. baumannii and its association with IS Aba1 and sequence types belonging to IC-II facilitates the successful dissemination of these extremely drug resistant strains.